Socioeconomic inequality in timing of ANC visit among pregnant women in Ethiopia, 2019 - Kidie, Atitegeb Abera; Asmamaw, Desale Bihonegn; Belachew, Tadele Biresaw; Fetene, Samrawit Mihret; Baykeda, Tsegaw Amare; Endawkie, Abel; Zegeye, Alebachew Ferede; Tamir, Tadesse Tarik; Wubante, Sisay Maru; Fentie, Elsa Awoke; Negash, Wubshet Debebe; Addis, Banchilay (Frontiers in Public Health, 2024)
Background Antenatal care (ANC) remains an invaluable approach to preventive care for ensuring maternal and infant health outcomes. Women in sub-Saharan Africa tend to delay their first antenatal care visits. In Ethiopia, only 20% of women received their first antenatal care during the first trimester of pregnancy. Timely and appropriate antenatal care practices can potentially save the lives of both mothers and children. Understanding socioeconomic inequality in the timing of antenatal care visits and its determinants may contribute to tackling disparities and achieving the sustainable development goals for maternal health. Objective This study aimed to assess the socioeconomic inequality in the timing of antenatal care visit. Method Secondary data sourced from the Mini Ethiopian Demographic Health Survey 2019 were used for this study. A total of 2,906 pregnant women were included in the study, and concentration curves were used to show inequality among sociodemographic and economic variables. Decomposition analysis was performed to estimate the contribution of each independent variable to the inequality in the timing of antenatal care visits. Result The estimate of early initiation of antenatal care was 63%. The concentration index was 0.18 (P < 0.001). The inequality in the timing of antenatal care visit was more concentrated among the wealthiest pregnant women with a concentration index value of 0.18 (P < 0.001). Based on decomposition analysis results, the wealth index (81.9%.), education status (22.29%), and region (0.0642%) were identified as contributing factors to the inequality in the timing of antenatal care visits among women. Conclusion The wealth index, educational status, and region were significant contributors to inequality in the early initiation of antenatal care visit. Improving women's wealth and education and narrowing the inequality gap are crucial for improving the health status of women and their children. We should focus on interventions targeted at early antenatal care visit to address the determinants of socioeconomic inequities.